Pelatihan Bahasa Inggris bagi Pengelola Satpam sebagai Upaya Meningkatkan Kualitas Komunikasi dalam Layanan Keamanan - Hastini; Bochari, Siska (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
English language proficiency is an essential skill in security services, particularly for security personnel (satpam) who frequently interact with foreign guests. This article describes an English training program for security supervisors as an empowerment strategy to enhance the quality of communication and security services. The training was conducted in the form of an interactive workshop using a Training for Trainers (ToT) approach, where security supervisors were trained to become effective tutors for the personnel under their supervision. The training materials covered basic communication in security contexts, English teaching techniques, and teaching practice through simulations and role-plays. Evaluation was carried out using pre-tests and post-tests to measure participants’ improvement in English proficiency and pedagogical skills. The results showed an increase in post-training scores in both communication and teaching abilities. This program is expected to generate a sustainable multiplier effect through internal training conducted by the security supervisors, thereby contributing to the overall improvement of professionalism and the quality of security services.